Socioemotional self- and co-regulation in functional seizures: comparing high and low posttraumatic stress - Roberts, Nicole A.; Villarreal, Lucia Dayana; Burleson, Mary H. (Frontiers in Psychiatry, 2023)
Functional seizures (FS) are seizure-like symptoms without electroencephalogram (EEG)-based epileptic activity. Those with FS often show emotion-related dysfunction and disrupted interpersonal relationships, in which posttraumatic stress disorder symptoms (PTS) may play a role. We sought to better understand trauma comorbidities and socioemotional processes in FS, including affectionate touch, a form of social connection linked to emotion regulation and awareness. We administered questionnaires online to a community sample of 89 trauma-exposed FS participants (FS diagnoses were self-reported), 51 with and 38 without clinical-level PTS (FS-PTShi, FS-PTSlo) and 216 seizure-free matched trauma-exposed controls (TCs), 91 with and 125 without clinical-level PTS (TC-PTShi, TC-PTSlo) per the Posttraumatic Stress Disorder Symptom Checklist (PCL). As hypothesized, both FS-PTShi and FS-PTSlo reported more emotional avoidance (Brief Experiential Avoidance Questionnaire), more emotion regulation difficulties (Difficulties in Emotion Regulation Scale), and more perceived stress (Perceived Stress Scale) than PTS-matched counterparts. FS-PTShi also reported less reappraisal (Emotion Regulation Questionnaire), more loneliness (UCLA Loneliness Scale), and less frequent affectionate touch (Physical Affection Scale) during waking and surrounding sleep than TC-PTShi, whereas FS-PTSlo and TC-PTSlo did not differ. Neither FS group differed from PTS-matched controls in emotion suppression (Emotion Regulation Questionnaire) or comfort with social touch (Social Touch Questionnaire). Among FS, FS-PTShi reported more difficulties than FS-PTSlo on nearly all measures (non-significant trend for social support). Findings underscore potential synergistic effects of FS and PTS clinical symptoms in shaping experiences of one’s emotions and social world, suggesting fostering meaningful connections with others, including via affectionate touch, is an important treatment target.